E-commerce Security in Bangladesh against Online Fraud and Cyber Crimes: : Legal Protections and Policy Recommendations - Mahmud, Arif; Sharmin, Tasnuva; Hoque, S.M. Saiful (The Jahangirnagar Review, 2025)
In this era of modern technology, online shopping has opened new doors of opportunity and E-commerce has become the new normal for many people. Because there is so much money involved in e-commerce transactions, fraudsters are attracted to them, therefore having an effective regulatory framework is crucial. Apart from the general statutes, the Bangladesh government has enacted the National Digital Commerce Policy, still, an effective e-commerce regulatory framework has not been established. This paper has analyzed the existing legal framework of Bangladesh against Ecommerce fraud and has provided recommendations for Creating an E-commerce Friendly Environment.